Is Active Purulence Associated With the Success of Particulate Autogenous Bone Grafting in the Reconstruction of Post-traumatic Mandibular Defects? A Retrospective Cohort Study - Pereira, Rodrigo dos Santos; Albieri, Fabrizio; Maikon de Sousa Santos, Anderson; Martins, Rodrigo dos Santos; Pessanha, Izabela Lopes; Mourão, Carlos Fernando (Journal of oral and maxillofacial surgery, 2025)
Bone defects following post-traumatic mandibular injuries represent a reconstructive challenge when active purulence is present. While particulate autogenous bone grafts are commonly used, their effectiveness in this context remains uncertain. The purpose of this study was to measure the association between active purulence and grafting success in post-traumatic mandibular defects reconstructed using particulate autogenous bone. A retrospective cohort study was conducted at the General Hospital of Nova Iguaçu from 2011 to 2023. The sample included subjects who underwent mandibular reconstruction for post-traumatic bony defects, regardless of purulence, with at least 6 months of follow-up. Exclusion criteria included prior radiotherapy or chemotherapy, uncontrolled systemic disease, oral communication ≥10 mm, or soft tissue loss requiring flap reconstruction. Presence or absence of purulent discharge at the bone defect site during bone reconstruction using particulate autogenous bone graft. The primary outcome was graft success, categorized as “Yes” for successful healing and “No” for graft failure. The secondary outcome was the occurrence of postoperative complications, also categorized as “Yes” for the presence of complications and “No” for their absence. Age, sex, race, mechanism of injury, defect location, post-traumatic complications, graft donor site, osteosynthesis material, and follow-up duration. Fisher exact test was used for categorical variables, and the t test or Mann–Whitney U test for continuous variables. Relative risks (RRs) with 95% CIs were reported. Significance was set at P < .05. The study included 27 subjects, with a mean age of 39.4 years (±12.5), and 23 (85.2%) were male. Active purulence was present in 16 (59.3%) subjects. Graft success was achieved in 23 (85.2%) subjects, with no significant association with purulence (RR = 1.2; 95% CI: 0.4 to 3.4; P = 1.0). A similar finding was observed for postoperative complications (RR = 0.6; 95% CI: 0.4 to 1.0; P = .30). Active purulence was not associated with graft failure or complications.